SPAWNING AND LARVAL DEVELOPMENT DOG CONCH (Strombus turturella) - Safar Dody (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Dog conch (Strombus turturella) is considered one of fishery commodities in Bangka Belitung Islands. This conch is often exploited and result in their populations are increasingly threatened. The aim of study to observe the reproduction and larval development of dog conch were studied under laboratory conditions. For the treatment of spawning the dog conch were placed in spawning tanks with a capacity of 1 ton. Stimulation of spawning is done by replacing the water in the tank as much as 90% every 24 hours until the eggs released by females. Spawning was preceded by copulation and fertilization occurs inside the female's body.The results showed that the first egg cell divides into two cells after two hours of spawning. Then each cell continues to divide into four cells to become multicellular and reach the gastrula stage after 48 hours. Free swimming larval phase for four days and then settle down along with the formation of the first shell. The larvae will grow up to 5 mm shell length for 20 days.Keywords: Dog conch, Strombus turturella, spawning, larva development